Principal Leadership Strategies in Building Quality Teacher Professionalism - Kurniasari, Anis Nila (Social Science Academic, 2025)
This study aims to analyze the strategies of school principals in improving teacher professionalism at Yayasan Pendidikan Islam Panjeng (YPIP) Panjeng. The research method used is qualitative with a case study approach, utilizing interviews, observations, and document analysis. The findings show that the principal at YPIP Panjeng implements leadership strategies, including structured academic supervision, teacher empowerment through training, and the development of collaborative school culture among teachers. The principal also adopts a transformational leadership style that focuses on motivation and support for teachers. However, challenges such as limited funding for training and resistance to change from some teachers remain obstacles in the implementation of these strategies. This study concludes that effective school leadership can enhance teacher professionalism, but continuous efforts are required to overcome the existing challenges for optimal results